Conceptual Design of a Robotic Ground-Aerial Vehicle with an Aeroelastic Wing Model for Mars Planetary Exploration - Wolduamlak Ayele; Victor Maldonado (Aerospace, 2023)
This paper presents the technical barriers and an analysis to advance the conceptual development of novel robotic ground-aerial vehicles (RGAVs) for exploration missions to Mars prior to human arrival and the establishment of a base. The concept for RGAVs for Mars planetary exploration is novel, and will require innovations that are at various stages of development or use by the aerospace community. The RGAV concept will utilize inflatable wing technology, which increases the flexibility of the wing, and thus the possibility of structural dynamic instabilities that must be studied in the context of the Martian atmosphere. An aeroelastic model for wing bending is proposed, which considers wind gusts where the change in wind direction is up to ±6° from the mean, and a turbulence intensity of up to 20%. Their effect on the bending displacement of a semi-elastic wing is quantified, resulting in a maximum wing tip displacement of 16.2 cm. Low-fidelity computational aerodynamic analysis is performed using OpenVSP (3.31.1, NASA, Washington, DC, USA) to compute mean aerodynamic loads during cruise conditions at a cruise Mach number of 0.70. Finally, a non-linear adaptive control system is proposed for the longitudinal aerial dynamics and a proportional integral derivative (PID) controller is outlined for the ground roving lateral dynamics.